Gastrointestinal symptoms in mastocytosis, is it only food hypersensitivity? - Osienicka, Patrycja; Niedoszytko, Marek; Romantowski, Jan (Alergologia Polska - Polish Journal of Allergology, 2025)
Mast cells (MC) are effector cells of most immediate allergic reactions. Patients suffering from mastocytosis (MS) have an increased number of MC, which can lead to severe hypersensitivity reactions (HR) after exposure to allergens. MC can also undergo degranulation spontaneously and in response to non-allergic stimulation. Additionally, in systemic mastocytosis, there is infiltration of tissues by MC, which can cause symptoms involving multiple organs, including the gastrointestinal (GI) tract. Gastrointestinal symptoms are one of the most common complaints reported by patients affected by this rare disease. Due to the nonspecific nature of gastrointestinal symptoms observed in patients with systemic mastocytosis, these symptoms may resemble other gastrointestinal disorders and are frequently misinterpreted as food allergies. The diagnosis and management of GI symptoms and food HR in patients with mastocytosis requires exceptional caution and multidisciplinary methods. This article is a review of current knowledge about MS with particular emphasis on gastrointestinal symptoms and food hypersensitivity reactions.